Antagonism of microRNA function in zebrafish embryos by using locked nucleic acid enzymes (LNAzymes) - Suryawanshi, Hemant; Lalwani, Mukesh Kumar; Ramasamy, Soundhar; Rana, Rajiv; Scaria, Vinod; Sivasubbu, Sridhar; Maiti, Souvik (Chembiochem, 2012)
MicroRNAs (miRNAs) have crucial functions in many cellular processes, such as differentiation, proliferation and apoptosis; aberrant expression of miRNAs has been linked to human diseases, including cancer. Tools that allow specific and efficient knockdown of miRNAs would be of immense importance for exploring miRNA function. Zebrafish serves as an excellent vertebrate model system to understand the functions of miRNAs involved in a variety of biological processes. We designed and employed a strategy based on locked nucleic acid enzymes (LNAzymes) for in vivo knockdown of miRNA in zebrafish embryos. We demonstrate that LNAzyme can efficiently knockdown miRNAs with minimal toxicity to the zebrafish embryos.
Keywords: enzymes; locked nucleic acids; microRNA; morpholino; zebrafish